The experiences of caregivers of children with epilepsy: A meta-synthesis of qualitative research studies - Yu, Zhichao; Shao, Qinwen; Hou, Kunhua; Wang, Yanjie; Sun, Xianghong (Frontiers in Psychiatry, 2022)
Objective Epilepsy is one of the most common chronic neurological disorders in children. The caregivers of these children bear heavy burden of care in the process of taking care of them. The objective of this metasynthesis was to explore the experiences and needs of caregivers of children with epilepsy. Methods and data sources Eight databases (PubMed, CINAHL, EMBASE, Web of Science, CNKI, Wanfang Data, VIP database, and CBM) were searched for qualitative studies from each database's inception to 31 June 2021. Studies were critically appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research. Qualitative data were extracted, summarized, and meta-synthesized. Results 13 studies were included, covering the data of 316 participants. 36 research results were extracted from these studies, which were combined into 11 categories, and finally formed 4 themes: (a) heavy burden of care; (b) emotional experience; (c) coping strategies; (d) care needs. Conclusion Caregivers beared a heavy burden of care and psychological burden. Despite the adoption of different coping strategies, their emotional distress was still very serious. Caregivers had unmet care needs. In order to improve caregivers' care capacity, the society and healthcare workers need to provide them with information support, psychological support, and take measures to create a friendly medical and living environment for them. Impact Understanding the experiences of caregivers of children with epilepsy will inform future research and practice. Healthcare workers could develop interventions to reduce caregiver burden and improve the level of caregivers' mental health. On the other hand, effective programs should be designed to improve caregivers' knowledge of the disease and enhance their ability to care. Society needs to take steps to improve the medical environment and the social stigma that is not friendly to epilepsy.